2005
DOI: 10.3997/1873-0604.2005043
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistivity imaging of tree trunks

Abstract: An electrical resistivity technique using a ring array of needle electrodes is applied to image the internal electrical structures of the trunks of living standing trees and trunk disks. Measured electrical resistance data are inverted using a 2D iterative finite-element algorithm which incorporates the cylindrical geometry of the trunk. The technique is successfully tested using synthetic models showing that the resolution obtained when mapping anomalous zones inside the trunk is higher for the dipole-dipole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…Increasing the number of electrodes can increase the resolution of inversion results (al Hagrey ). Ideally, the spacing between each two adjacent electrodes should be smaller than the actual sapwood width (Guyot et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Increasing the number of electrodes can increase the resolution of inversion results (al Hagrey ). Ideally, the spacing between each two adjacent electrodes should be smaller than the actual sapwood width (Guyot et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Electrical resistivity for one selected tree of each species is given in Figure . The same typical R s spatial distribution pattern is observed for each tree as illustrated by al Hagrey (), that is, high R s in the trunk centre (heartwood) decreasing toward the outer layers (sapwood and wet bark). These trees have different diameters, which can be observed from the axes.…”
Section: Resultsmentioning
confidence: 99%
“…Electrical resistivity tomography using multi-electrode arrays on the surface or in small boreholes can be successfully applied to generate images of root zones reflecting their spatial variability and to quantify their biomass (Amato et al 2008;Amato et al 2009;Petersen and Al-Hagrey 2009) or to study the water flow in soil and plants (Pagès et al 2000). Other applications of electrical resistivity tomography using ring electrode arrays around a trunk aim at a detailed investigation of living trees (Al-Hagrey 2006;Nicolotti et al 2003;Weihs et al 1999). The resulting horizontal cross-sections of the conductivity distribution can be used to monitor the sap flow and to recognise decay processes in the trunk.…”
Section: Introductionmentioning
confidence: 99%
“…Like Stamm (), we found that wood moisture content can supersede species identity as a determinant of electrical resistivity. Although the important role of moisture in wood resistivity is well established (Al Hagrey, ; Carter & Blanchard, ; Gora & Yanoviak, ), no other studies have compared moisture‐resistivity patterns among growth forms or trees in situ.…”
Section: Discussionmentioning
confidence: 99%